The Comparison of Biodistribution, Efficacy and Toxicity of Two PEGylated Liposomal Doxorubicin Formulations in Mice Bearing C-26 Colon Carcinoma: a Preclinical Study - Razavi-Azarkhiavi, K.; Jafarian, A. H.; Abnous, K.; Razavi, B. M.; Shirani, K.; Zeinali, M.; Jaafari, M. R.; Karimi, G. (Drug Research, 2016)
Background: Over the past several years, the considerable attention has been progressively given to liposomal formulations of anthracyclines. SinaDoxosome® (Exir Nano Sina Company, Iran) is a pegylated liposomal doxorubicin (DOX) which approved by Food and Drug Administration of IRAN for treatment of some types of cancer. The aim of this study was to compare the biodistribution, efficacy, cardiotoxicity and hepatotoxicity of SinaDoxosome® with Caelyx® in mice bearing C-26 colon carcinoma.Methods and results: Mice tumor size evaluation during the experimental period (28 days) showed comparable therapeutic efficacy of nano-formulations. The biodistribution studies showed no significant difference in DOX tissue concentration between Caelyx® and SinaDoxosome®. DOX induced-ECG changes were not detected in nano-formulations. No significant alteration was found in biochemical indexes of myocardial injury in mice exposed to nano-formulations in comparison with control mice. The tissue oxidative parameters such as lipid peroxidation, glutathione, catalase and superoxide dismutase was significantly changed as the results of free DOX treatment. However, the oxidative status of Caelyx® and SinaDoxosome® treated animals did not showed any changes. The experiment also revealed that apoptotic pathway was not activated in the heart of mice exposed to nano-formulations.Conclusions: Although this investigation showed that Caelyx® and SinaDoxosome® are similar in terms of biodistribution, efficacy and toxicity, appropriate clinical evaluations in patients should be considered.
Keywords: caelyx®; sinadoxosome®; biodistribution; cardiotoxicity; oxidative stress